Kajian Inbreeding Terhadap Fenotip Lalat Buah (Drosophila sp) Tipe Liar (Jurnal Pilar Sains, 2003)
The purpose of this research is to examine the effect and heritability inbreeding to fruit fly phenotype(Drosophila sp) in wild type. This research works on July – September 2001 in laboratory Biologic FKIPUNRI Pekanbaru. Design used completely randomized design consist of 5 mating patterns: outbreeding(P0), ful sib (P1) half sib (P2), uncle naice (P 3) and parent offspring mating patterns (P4) with 3 replication.The phenothype with observation: population, viability, abdomen lengh and wing lengh. The phephenotypes were analized using ANOVA with Duncan’s Multiple Rang Test (DMRT) the viability of thetest was 5% and genetics analysis regresi Strickberger 1962. The result of this research showed that effectinbreeding with mating pattern variance significant to phenotype all. Reduction highly occurred at parentoffspring mating pattern. Heritability inbreeding varience to phenotype all. Heritability highly occurred athalf sib mating pattern.